Electrochemical Peroxidation Method for Reduction of Chemical Oxygen Demand (COD) Carbofuran in Furadan 3GR Pesticides - Ayu Sri Wahyuni; Suhartana Suhartana; Damar Nurwahyu Bima (Universitas Diponegoro, 2021)
Carbofuran is a pollutant compound derived from the pesticide Furadan 3GR which is widely used in agriculture. Various methods of carbofuran degradation have been carried out, one of which is the conventional electrochemical method. This study used an electrochemical peroxidation process to degrade Carbofuran in the pesticide Furadan 3GR. This study aims to determine the optimum conditions (time, Na2SO4 concentration, and volume addition of H2O2) for electrochemical peroxidation and to compare the effectiveness of electrochemical and electrochemical peroxidation methods by measuring the parameter of carbofuran COD reduction. The significance of the electrochemical peroxidation method and the conventional electrochemical method was compared as a preliminary test. The COD reduction of Carbofuran using traditional electrochemical methods and electrochemical peroxidation was 45.76% and 88.70%, respectively. Batch carbofuran electrochemical peroxidation process was accomplished to ascertain the optimum conditions under various operation times, the concentration of Na2SO4, and the additional volume of H2O2. The largest COD reduction of 93.78% was obtained at 10 minutes, 75 mM Na2SO4, and 2 mL H2O2. The UV-Vis spectrophotometric absorption of Carbofuran at a wavelength of 274 nm was significantly reduced from 1.377 to 0.131 at optimum conditions. The IR spectrum measurement results indicate a reduction in absorbance for the N-H group (3383 cm-1) and the C=O group (1643 cm-1) at optimum conditions. Overall, the electrochemical peroxidation process proved to be an appropriate technique for COD reduction of Carbofuran in Furadan 3GR pesticides.